Exploring the impact of flipped classroom model on enhancing learning outcomes in economics: a review of scholarly perspectives - Darobi, Muhammad; Kristiani, Kristiani; Harini, Harini (2023)
Effective education plays a crucial role in the development of students' knowledge and skills. Learning models continue to evolve in pursuit of better learning outcomes. One innovative approach receiving attention is the Flipped Classroom learning model. This article explores the impact of implementing the Flipped Classroom model on enchancing Economics learning outcomes. Through a deep scientific perspective, it presents a comprehensive literature review. This study discusses the implementation method, changes in students-teacher interactions, and the measurement of learning perfoermance. The Flipped Classroom is capable of facilitating active, collaborative, and self-directed learning, thereby improving students' understanding of concepts, critical analysis, and engagement in Economics. It also addresses challenges, such as meticulous material preparation and technology availability. The results offer valuable insight for educational practitioners, curriculum developers, and researchers who are interested in implementing the Flipped Classroom model to enchange economics education. While further research is needed to measure long-term impact and supporting success factors, this article stimulates in-depth discussion regarding the potential and obstacles of implementing the Flipped Classroom in the context of economic education. Keyword: Flipped Classroom, learning outcomes, economics, literature review, effective learning